The Role of ecologicals in ecological footprint quality :|empirical evidence from Turkey - Köksal, Cihat. (Thesis (M.A.) - Bogazici University. Institute for Graduate Studies in the Social Sciences, 2019., 2019)
With this study, the role of shadow economies in ecological footprint levels is intended to be investigated for the case of Turkey. Annual data that ranges from 1961 to 2014 has been selected with this respect. Results of this study confirm the long-term effects of shadow economic activities on the levels of ecological footprint in Turkey. It is found that the volume of shadow economies exerts positively significant and elastic effects on ecological footprint; that is, one percent change in shadow economic activities leads to one percent change in ecological footprint in the same directions. Therefore, this study reaches a significant conclusion that shadow economies in Turkey are long-term and vital drivers of environmental pollution in the case of Turkey. In order to acquire Turkey’s historical background, demographic information and foreign trade on environmental degradation, an ecological footprint-income model with variables such as energy consumption, urbanization, financial development, real exchange rate, and trade openness have been augmented. The empirical conclusions reveal that the Environmental Kuznets Curve (EKC) hypothesis holds in the long-run. All variables except urbanization have also been found statistically significant on ecological footprints of Turkey.
Keywords: Informal sector (Economics); Nature -- Effect of human beings on -- Turkey.; Environmental protection -- Turkey.